The Activity of Political Science Researchers in Public Debate: Case Study of Poland - Sroka, Anna (Political Preferences, 2021)
This article has several aims. With the help of the original survey data, the article will analyse how Polish political scientists perceive the presence of members of their own scholarly discipline in public debate as desirable and what are their opinions on it. Secondly, the article determines to what extent the political changes initiated in 2015 have affected the general approach to media appearances, and assessments of their content and frequency. Thirdly, an attempt will also be made to determine to what extent the political convictions of political science researchers are correlated with the general assessment of the presence of researchers in public debate, the choice of media in which they are active, and the frequency of their appearances.